Inspection method for cable assembly quality based on AR virtual-real image attention mechanism - Ganlin ZHAO; Chang YU; Jianfu ZHANG; Jianxin YANG; Pingfa FENG; Qun SHEN (物联网学报, 2021)
Cable assembly in spacecraft occupies a large proportion in the final assembly process, and the quality of cable assembly directly affects the working performance of the whole product.The existing augmented reality-assisted cable assembly system lacks the ability to make real-time judgment and feedback on the assembly results, and cannot identify whether the currently assembled cable meets the quality requirements.In order to solve the above problems, a cable assembly quality inspection method based on AR virtual-real image attention mechanism was proposed.Critical areas in the captured images were located and detected by constructing virtual assist models to filter redundant image information.Based on YOLOv4-Tiny image detection model, the key node location of assembled cable was judged.The overlap of the laying path was obtained based on the method of calculating the average overlap of the neighborhood, and the bending radius of the cable was derived based on the method of camera inverse projection.Finally, an augmented reality-based cable assembly quality inspection system was developed using HoloLens2.The quality inspection was performed on the four designed cable assembly cases, and the feasibility and effectiveness of the method and system were experimentally verified.